Spatio-Temporal Variation Characteristics and Influencing Factors of Vegetation Cover in Loess Plateau Based on Model of Spatial Autocorrelation and Geodetector - Gao, Jiawei; Xue, Jincheng (Transactions on Environment, Energy and Earth Sciences, 2024)
The Loess Plateau is located in the transition zone between subhumid, arid and semi-arid in China, where water resources are rare and ecological environment are fragile. Since 1999, the large-scale “Grain For Green” project has improved environment significantly. On the basis of summarizing the spatial variation characteristics of vegetation cover in the region, this study used spatial autocorrelation to analyze the correlation between Net Primary Production(NPP), precipitation and vegetation cover change. Natural factors such as temperature, precipitation, Digital Elevation Model(DEM) and soil moisture and human factors such as population density, Gross Domestic Production (GDP), road density and grain yield NPP were statistically divided by geodetector. The influence degree of each driving factor on Normalized Difference Vegetation Index (NDVI) was systematically discussed, and the spatial-temporal variation characteristics of vegetation in the basin and the driving force of the driving factors were explored.